Langkah Taktis Pemerintah Daerah Dalam Pencegahan Penyebaran Virus Corona Covid-19 di Indonesia - Zahrotunnimah Zahrotunnimah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
Abstract Since the World Health Organization or WHO has declared the Corona Covid-19 virus a pandemic. Following up on this, the Indonesian government also stated that the Corona virus problem had become a non-natural national disaster. The President of the Republic of Indonesia and the Regional Government along with their staffs provided each other hand in hand to make some tactical steps as an effort to prevent the spread of Corona Covid-19 Virus in the community. From the ministerial level to the heads of the provinces, regencies and even the municipal government. This research uses content analysis method, where content analysis is limited to newspaper media that deliver information related to some tactical steps taken by each head of government, both in several regions and countries. The purpose of this study is to provide education to the public in facing global disasters and their prevention. The results showed that local governments have done a lot of communication strategies to their respective regional communities through coercive, informative, canalizing, educative, persuasive and redundancy techniques in packaging messages in the form of instructions, appeals to the public to prevent Covid-19 transmission in their respective regions. . However, there is still no coercive technique up to the stage of imposing sanctions for deterrent effects for offenders. The central government also has not yet maximized its role in using a comprehensive communication strategy for all local governments. This is because there is no national command from the central government which is known to be slow in preventing the transmission of Covid-19 which has become a global disaster.Keywords: Tactical Steps, Local Government, Corona Virus Abstrak:Sejak Badan kesehatan Dunia atau WHO telah menyatakan bahwa virus Corona Covid-19 sebagai pandemi. Menindaklanjuti hal tersebut, pemerintah Indonesia juga menyatakan masalah virus Corona sudah menjadi bencana nasional non alam. Presiden Republik Indonesia dan Pemerintah Daerah beserta jajarannya memberikan untuk saling bahu membahu membuat beberapa langkah taktis sebagai upaya pencegahan penyebaran Virus Corona Covid-19 di masyarakat. Dari level menteri sampai kepala daerah Provinsi, Kabupaten bahkan Pemkot. Penelitian Ini menggunakan metode analisis isi, dimana content analisis dibatasi pada media surat kabar yang menyampaikan informasi terkait beberapa langkah taktis yang diambil oleh masing-masing kepala pemerintahan, baik di beberapa daerah maupun negara. Tujuan penelitian ini untuk memberikan edukasi kepada masyarakat dalam menghadapi bencana global dan pencegahannya. Hasil penelitian menunjukkan bahwa pemerintah daerah telah banyak melakukan stategi komunikasi kepada masyarakat wilayahnya masing-masing melalui teknik koersif, informatif, canalizing, edukatif, persuasif dan redudancy dalam mengemas pesan berupa instruksi, himbauan kepada masyarakat untuk mencegah penularan Covid-19 di wilayahnya masing-masing. Akan tetapi masih belum melakukan teknik koersif sampai pada tahap memberikan sanksi untuk efek jera bagi pelanggarnya. Pemerintah pusat juga belum memaksimalkan perannya dalam menggunakan strategi komunikasi secara komprehensif bagi seluruh pemerintah daerah. Hal ini karena tidak adanya komando nasional dari pemerintah pusat yang dikenal lambat dalam mencegah penularan Covid-19 yang sudah menjadi bencana global.Kata Kunci: Langkah Taktis, Pemerintah Daerah, Virus Corona